Audit dan Analisis Energi Listrik di Hotel Bali Dinasty Resort - Yogi Iswara, I Gede; Wijaya Kusuma, I.G.B; Dwi Budiana Penindra, I Made (Teknik Desain Mekanika; Vol 10 No 2 (2021): April 2021 : Teknik Desain Mekanika, 2021)
Abstract This study aims to carry out energy audit activities and perform calculations for the value of Energy Consumption Intensity (IKE) at the Bali Dinasty Resort Hotel. With direct field observations and interviews with the hotel for the data collection method, all data for the audit process and IKE calculations can be obtained. Based on the research that has been carried out at the Bali Dinasty Resort Hotel, conclusions can be drawn (1) The energy audit activity is carried out to identify the amount of energy used by the Bali Dinasty Resort Hotel, then calculates the Energy Consumption Intensity (IKE) to determine the wasteful or economical use of its energy. (2) The level of energy consumption at Bali Dinasty Resort Hotel varies every month. The known IKE values include the NPW building of 9.18 kWh / m2 / month, the NGW building of 11.12 kWh / m2 / month, the SPW building of 7.79 kWh / m2 / month, the SGW building of 8.15 kWh / m2 / month, and building BW of 10.20 kWh / m2 / month. With the IKE value as calculated for the 5 buildings, the energy use can be categorized as “efficient”. As for the suggestions that can be given, namely (1) Replacing electronic devices that consume a lot of energy both individually and in large quantities to maintain efficient use of electrical energy (2) Socializing about electricity-saving behavior to all parties in the aspect of not reducing comfort (3) Conduct monthly audits as a reference for whether the hotel is successful in reducing energy consumption each month, so that action can be taken or to continue to improve energy efficiency without reducing the comfort provided by the hotel to guest visitors. Keywords: Energy Audit, IKE